Patient Race, Reported Problems in Using Glaucoma Medications, and Adherence. (21st November 2012) - Sleath, Betsy; Blalock, Susan J.; Covert, David; Skinner, Asheley Cockrell; Muir, Kelly W.; Robin, Alan L.
Abstract : Objective . The objectives of the study were to (a) describe various factors potentially related to objectively measured adherence to glaucoma medications and self-reported glaucoma medication adherence self-efficacy and (b) examine the relationship between patient race, the number of patient reported-problems, and adherence in taking their glaucoma medication. This was a cross-sectional study conducted at two glaucoma subspecialist referral ophthalmology practices. Methods . We measured subjects' reported problems in using glaucoma medications, adherence to glaucoma medications utilizing the Medication Events Monitoring System (MEMS) devices, and general glaucoma medication adherence self-efficacy using a previously validated 10-item scale. Multivariable logistic and linear regression was used to analyze the data. Results . Seventy-one percent of patients self-reported at least one problem in using their glaucoma medications. White patients were more than 3 times more likely to be 80% adherent in using their glaucoma medications than non-White patients. Patients who had glaucoma longer reported significantly higher glaucoma medication adherence self-efficacy. Patients who reported more problems in using their medications had significantly lower glaucoma medication adherence self-efficacy. Conclusions . Eye care providers should assess patient reported problems and glaucoma medication adherence self-efficacy and work with patients to find ways to reduce the number of problems that patients experience to increase their self-efficacy in using glaucoma medications.